Analyzing the investments strategies for renewable energies based on multi-criteria decision model - Zhong, Jianlan; Hu, Xuelong; Yüksel, Serhat; Dinçer, Hasan; Ubay, Gözde Gülseven (IEEE-Institute of Electrical and Electronics Engineers Inc, 2020)
The purpose of this study is to determine appropriate innovative strategies for the renewable energy investments. For this purpose, a hybrid multi-criteria decision-making (MCDM) model is proposed based on interval type-2 (IT2) fuzzy sets and alpha cut levels. Within this context, hesitant IT2 fuzzy DEMATEL-Based Analytic Network Process (DANP) with alpha cut levels is applied for weighting the customer requirements. Moreover, hesitant IT2 fuzzy technique for order preference by similarity to ideal solution (TOPSIS) with alpha cut levels is used for ranking the TRIZ-based strategies priorities of renewable energy investments based on house of quality technique. These strategies are also ranked with hesitant IT2 fuzzy Vise Kriterijumska Optimizacija I Kompromisno Resenje (VIKOR) approach to make a comparative evaluation. The results illustrate that ease of access and security are among the most prominent factors of customer requirements for renewable energy investments. It is also identified that innovative technical requirement entitled cushion in advance has the best choice for the sustainable renewable energy projects. Furthermore, the results of proposed model using hesitant IT2 fuzzy DANP and hesitant IT2 fuzzy TOPSIS are identical for the different levels of alpha cut. In addition, it is also defined that the results of hesitant IT2 fuzzy TOPSIS and hesitant IT2 fuzzy VIKOR are quite coherent. This is a clear evidence that the proposed model is coherent and could provide comprehensive results for the future studies. It is strongly recommended that a detailed analysis is required to identify the risks in renewable energy investment projects. Hence, necessary actions can be taken appropriately so that it can be possible to prevent problems before they grow.
Keywords: TRIZ; House of Quality; Hesitant IT2 Fuzzy DEMATEL; Hesitant IT2 Fuzzy TOPSIS; Renewable Energy; Strategy Development